Analisis Faktor-Faktor yang Mempengaruhi Asset Misappropriation Berdasarkan Fraud Diamond Theory: Studi Kasus pada PT. XYZ - Anggi Yunita Priyadi; Indra Cahya Kusuma; Ayi Jamaludin Aziz (AKUNTANSI 45, 2025)
This research aims to make an analysis of the factors that influence asset misappropriation based on the Fraud Diamond Theory, with a focus on pressure, opportunity, rationalization, and capability as the main variables. Using a quantitative approach, data was collected from employees of PT XYZ through a survey-based questionnaire. This study used multiple linear regression analysis through JASP 0.14.1.0 to test the relationship between these factors and asset misappropriation. The research findings prove that 2 variables namely pressure and opportunity have a positive and significant effect on asset misuse and the other 2 variables namely rationalization and ability have no effect on asset misuse.